Matematyczne ciało. Wprowadzenie do teorii matematyki ucieleśnionej - Karoń, Aleksandra Irena (Humaniora. Czasopismo Internetowe, 2021)
Mathematics as a field of knowledge and culture presents researchers with many problems, also of a philosophical nature. One of the issues worth considering when considering the nature of mathematics is the theory of embodied mathematics, which links abstract mathematical thinking with the functioning of the human body in its purely physical dimension. This theory, on the one hand, uncovers new information about the yet unknown neural correlates of mathematics, and on the other hand, it poses important philosophical and cultural questions about the place of mathematics and its role in discovering the rules of reality.